Community Role in Ecotourism Development to Improve Local Economy - Rully Khairul Anwar; Mohammad Taufiq Rahman; Yunus Winoto (Khazanah Sosial, 2023)
Situ Cisanti is one of the hundreds of ecotourism objects in Indonesia. The local Government's ecotourism development continues to intensify by involving the surrounding community in Tarumajaya Village. This study focuses on the role of the community around Situ Cisanti in the development of ecotourism to improve the local economy. Using qualitative methods and interviewing some participants, the results of this study found that the community around Situ Cisanti has actively participated in ecotourism development activities. This is evidenced by the high level of community enthusiasm when participating in community role optimization activities organized by the Government and local managers. In addition, in terms of the economic aspect, the community around Situ Cisanti shows an increase. This is demonstrated by the concrete actions of the community who have become economic actors around the Situ Cisanti ecotourism object. The community takes advantage of the existence of tourism in the form of stalls, culinary, coffee, souvenirs and homestays owned by local communities. The most use of ecotourism is in the form of recruitment of casual daily employees, construction workers, shop businesses, coffee businesses, culinary businesses, souvenir businesses, parking businesses and motorcycle taxis. This research contributes mainly to researchers and policy makers about the integration of community participation management in the development of ecotourism in various locations in Indonesia.